Hermetic bag for the storage of maize: Economic perspective in different Sub-Saharan African countries, food security and greenhouse gas emissions - Dijkink, Bert; Broeze, Jan; Axmann, Heike; Vollebregt, Martijntje (2019)
During storage, cereals and legumes are vulnerable to insects, rodents and fungi which can cause toxins formation, discoloration, damage and/or weight loss of the product. Hermetic bags prevent excessive insect infestation. The effects of hermetic bags for the storage of maize on food loss reduction and its effect on net greenhouse gas (GHG) emissions are assessed from field trials. The economic effects are analysed in different Sub-Saharan Africa countries. In data used from field trial typically, beyond 100 days significant losses occur with standard storage whereas with hermetic bags product losses are kept to a minimum. From an economic point of view the situation is more complex; interventions effectiveness depends mainly on the seasonal price fluctuation of the commodity. For own consumption, when the quality is less important, the use of hermetic bags is only more economical compared to other ways of storage after 100 days. As the quality of maize is well preserved by the hermetic bag, the return on the investment is faster when the maize is sold at the market. However, for countries with a low seasonal price gap the investment cannot be earned back.